Real-world data on managing patients with coronary artery disease and multifocal atherosclerosis. Results of the 12-month international clinical registry of patients with identified multifocal atherosclerosis in the Russian Federation and Eurasian countries (KAMMA) - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; T. I. Batluk; N. A. Koziolova; A. I. Chesnikova; A. Y. Vaskin; D. S. Tokmin; I. G. Bakulin; O. L. Barbarash; N. Y. Grigoryeva; I. V. Gubareva; et al. (Российский кардиологический журнал, 2025)
Aim. To study real-world data on managing patients with coronary artery disease (CAD) and multifocal atherosclerosis (MFA) for 12 months by outpatient cardiologists.Material and methods. KAMMA is a real-world registry organized by the Eurasian Association of Therapists. The main branch included men and women over 18 years of age with confirmed atherosclerosis in two or more arterial systems and one or more risk factors for atherosclerosis. The start date for patient recruitment was February 1, 2022 and the end date was November 27, 2022. The design included 3 following visits: 1 — baseline, 2 — after 6 months, 3 — after 12 months. Twentyeight research centers were located in 7 federal districts of the Russian Federation, as well as in the Republics of Kazakhstan, Uzbekistan and Belarus.Results. A patient population (n=2905) was formed, all of whom had verified CAD. The mean age was 66,0 [59,0; 72,0] years (men — 60,3%). Low-density lipoprotein cholesterol decreased by 20,4% over 12 months, while non-high-density lipoprotein cholesterol — by 12,7%. Over 12 months, lipid-lowering therapy did not undergo significant changes. Statin monotherapy was maintained in 83%, of which only 53,7% of patients received high-dose therapy. Combined statin+ezetimibe therapy was used in 12,4%, while statin+ezetimibe+PCSK9 inhibitor — in 4,6%. During the 1-year follow-up, antithrombotic therapy was not enhanced. Low prescription rate of combination therapy with antiplatelet agents (15,7%) and low-dose rivaroxaban and acetylsalicylic acid (7,9%) remained. By the follow-up end, a high incidence of major adverse cardiovascular events (8,8%) was registered in patients included in the KAMMA registry.Conclusion. Despite the fact that patients with MFA have a very high cardiovascular risk, routine management of these patients is characterized by high clinical inertia. During the 1-year follow-up, lipid-lowering and antithrombotic therapy was not properly strengthened, due to which the target levels of key lipid profile parameters were not achieved and a high rate of major adverse cardiovascular events was observed in patients included in the registry.